LAS ÁREAS DE ACTIVIDAD EN LA UNIDAD RESIDENCIAL PREHISPÁNICA: PROPUESTA DE CONCEPTUALIZACIÓN PARA SU CLASIFICACIÓN, MÁS ALLÁ DE “LO DOMÉSTICO” - Noel Espinoza, Arturo Juan (2017)
Summary a theoretical-methodological proposal for conceptualizing classification units referred to areas of activity that can be identified in association with prehispanic residential units of the Central Andes, as a result of formal and functional analysis of a representative sample of archaeological reports presented.The conceptual definition of the residential unit is complemented by the characterization of other categories, allowing the description of contexts of activity areas inside (including the household); which allow to increase the content of environment inferences social relations of economic production and biological reproduction of those social groups that developed in the different natural regions of the Central Andes.